Temporal profiling of cytokines in passively expressed sweat for detection of infection using wearable device - Jagannath, Badrinath; Lin, Kai‐Chun; Pali, Madhavi; Sankhala, Devangsingh; Muthukumar, Sriram; Prasad, Shalini (Bioengineering & translational medicine, 2021)
This work presents the viability of passive eccrine sweat as a functional biofluid toward tracking the human body's inflammatory response. Cytokines are biomarkers that orchestrate the manifestation and progression of an infection/inflammatory event. Hence, noninvasive, real‐time monitoring of cytokines can be pivotal in assessing the progression of infection/inflammatory event, which may be feasible through monitoring of host immune markers in eccrine sweat. This work is the first experimental proof demonstrating the ability to detect inflammation/infection such as fever, FLU directly from passively expressed sweat in human subjects using a wearable “SWEATSENSER” device. The developed SWEATSENSER device demonstrates stable, real‐time monitoring of inflammatory cytokines in passive sweat. An accuracy of >90% and specificity >95% was achieved using SWEATSENSER for a panel of cytokines (interleukin‐6, interleukin‐8, interleukin‐10, and tumor necrosis factor‐α) over an analytical range of 0.2–200 pg mL−1. The SWEATSENSER demonstrated a correlation of Pearson's r > 0.98 for the study biomarkers in a cohort of 26 subjects when correlated with standard reference method. Comparable IL‐8 levels (2–15 pg mL−1) between systemic circulation (serum) and eccrine sweat through clinical studies in a cohort of 15 subjects, and the ability to distinguish healthy and sick (infection) cohort using inflammatory cytokines in sweat provides pioneering evidence of the SWEATSENSER technology for noninvasive tracking of host immune response biomarkers. Such a wearable device can offer significant strides in improving prognosis and provide personalized therapeutic treatment for several inflammatory/infectious diseases.